MENISCUS RESECTION AND REPAIR AS A MODERN-DAY TRAUMA. INNOVATIVE USE OF THE DRY NEEDLING METHOD - Павлова, Тетяна; Глибовець, Аліна (SWorldJournal, 2026)
The article examines current issues regarding surgical intervention for the treatment of a damaged meniscus and modern techniques in the recovery period from the perspective of rehabilitation intervention. An overview and comparison between meniscus resec